Assessment of ground water potentiality in semi-arid area of central Tanzania. implication from geology and geomorphology of the dodoman supergroup - Godson Godfray; Malugu M. Tembo (Geology, Ecology, and Landscapes, 2024)
ABSTRACTSemiarid areas face challenges in the availability of water for domestic, agricultural and industrial use. The freshwater availability in semi-arid is limited due to low periods of rainfall and high evaporation rate. Groundwater resource is the only promising source of freshwater in semi-arid regions. The increased demand for freshwater in the semiarid region has increased the demand for groundwater exploration. The availability of groundwater in the subsurface is influenced by the subsurface geology, geomorphological properties and climatical condition of the region. This review aimed to analyse and combine pieces of available information on groundwater potential assessments in the central part of Tanzania. Central TANZANIA is within the craton basement rocks, where most aquifers are crystalline and fractured crystalline rocks. The groundwater origin, movement and existence rely upon numerous geomorphological and geological factors. Because of the terrain's geology and the compartmentalization of aquifers, determining the groundwater potential is difficult in basement terrain. Studying the geomorphology and geology of groundwater recharge zones is the key to exploring groundwater availability. The integration of geomorphological, geological and geophysical information yields a promising groundwater potential zone for placement of a well. The selection of the geophysical methods depends on the nature and geology of the area. Electrical Resistivity Tomography (ERT) can be utilized in combination with other geophysical methods in fractured and weathered crystalline rocks in the semiarid environment, as in the Dodoma region, because it is the best geophysical tool for groundwater exploration in the fractured aquifer.